Transformation of Intergenerational Communication Behaviour and Ethics in the Office Environment - Nazla Annindya Renanta; Rahma Ardiyanti (International Journal Administration, Business & Organization, 2026)
Generational differences in the workplace present both challenges and opportunities for organisations to build effective communication and a balanced working environment. This topic was chosen because younger employees entering the workforce are bringing perspectives and communication styles that differ from those of previous generations. This study aims to explore how intergenerational communication behaviour and ethics are formed in office settings, and how interactions across age groups contribute to workplace harmony. The research employs a qualitative descriptive approach through literature review, observation, and interviews with employees from various generations. The findings reveal that communication differences between younger and older generations can be bridged through mutual understanding and willingness to adapt to each other’s communication patterns. Younger generations tend to communicate more openly and adapt quickly to digital platforms, while older generations emphasise politeness, structure, and experience. When both groups interact, a new form of communication emerges, one that is more open, respectful, and built on mutual trust. Ethical communication has also evolved from formal rules into a shared awareness of communicating wisely and professionally. This study is expected to provide organisations with insights into fostering a more harmonious and collaborative multigenerational work culture.